2020
DOI: 10.1042/bsr20200654
|View full text |Cite
|
Sign up to set email alerts
|

Combined dimercaptosuccinic acid and zinc treatment in neurological Wilson’s disease patients with penicillamine-induced allergy or early neurological deterioration

Abstract: The clinical data of safety and efficacy of a combined treatment with dimercaptosuccinic acid (DMSA) and Zinc with two years’ follow-up in 60 neurological Wilson’s disease (WD) patients was retrospectively analyzed. All the patients included in this study were newly diagnosed and initialized with D-penicillamine (DPA) treatment but were found to have either neurological deterioration or allergy, and their treatment was switched to a combined treatment of DMSA and Zinc. Fifty one patients (85%) had the neurolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A clinical study by Zhu et al, reported that the patients with Wilson disease were given D-penicillamine (DPA) medication at first, but later they developed neurological symptoms as well as allergies. 38 We can see that these medications can cause a variety of allergic reactions in patients, some of which can be fatal. To prevent these problems, there is a need for predicting the allergenicity of chemical compounds before using them for treatment purposes.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study by Zhu et al, reported that the patients with Wilson disease were given D-penicillamine (DPA) medication at first, but later they developed neurological symptoms as well as allergies. 38 We can see that these medications can cause a variety of allergic reactions in patients, some of which can be fatal. To prevent these problems, there is a need for predicting the allergenicity of chemical compounds before using them for treatment purposes.…”
Section: Discussionmentioning
confidence: 99%
“…FDA-approved drugs analysis have shown that few drugs which are used for treatment of certain diseases, are also causing allergy as the side effect. Literature evidences have shown that administration of FDA-approved drugs such as, Cefuroxime 36 , Spironolactone 37 , Penicillamine 38 can cause allergic reactions like, skin allergies, anaphylactic reactions, hypersensitivity. For instance, a case report has shown that 60 year old patient was experiencing anaphylactic reaction after given an antibiotic cefuroxime.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study by Zhu et al, reported that the patients with Wilson disease were given D-penicillamine (DPA) medication at first, but later they developed neurological symptoms as well as allergies. 38…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no significant difference in long-term therapy [ 27 ]. Another study in 60 neurological WD patients observed that combination therapy of DMSA and zinc effectively improved the neurological symptoms of those with a history of neurological deterioration with D-penicillamine [ 28 ]. Over one to two years of treatment, 85% of patients showed improvement, 11.67% experienced a stable neurological condition, and 3.33% suffered deterioration of neurological symptoms [ 28 ].…”
Section: Reviewmentioning
confidence: 99%